Case Report: Chorea-Acanthocytosis Presents as Epilepsy in a Consanguineous Family With a Nonsense Mutation of in VPS13A - Luo, Fang-Mei; Deng, Ming-Xing; Yu, Rong; Liu, Lv; Fan, Liang-Liang (Frontiers in Neuroscience, 2021)
Chorea-Acanthocytosis (ChAc), a rare autosomal recessive inherited neurological disorder, originated from variants in Vacuolar Protein Sorting 13 homolog A (VPS13A) gene. The main symptoms of ChAc contain hyperkinetic movements, seizures, cognitive impairment, neuropsychiatric symptoms, elevated serum biochemical indicators and acanthocytes detection in peripheral blood smear. Recently, researchers found that epilepsy may be a presenting and prominent symptom of ChAc. Here, we enrolled a consanguineous family with epilepsy and non-coordinated movement. Whole exome sequencing was employed to explore the genetic lesion of the family. After data filtering, co-separation analysis was performed by Sanger sequencing and bioinformatics analysis, the homozygous nonsense variant (NM_033305.2: c.8282C>G, p.S2761X) of VPS13A were identified which could be genetic factor of the patient. No other meaningful mutations were detected. This mutation (p.S2761X) led to a truncated protein in exon 60 of the VPS13A gene, was simultaneously absent in our 200 local control participants. The homozygous mutation (NM_033305.2: c.8282C>G, p.S2761X) of VPS13A may be the first time be identified in ChAc patient with epilepsy. Our study assisted to the diagnosis of ChAc in this patient and contributed to the genetic diagnosis and counseling of families with ChAc presented as epilepsy. Moreover, we further indicated that epilepsy was a crucial phenotype in ChAc patients caused by VPS13A mutations.